Fuzzy models presentation and realization by means of relational systems - Filatov, V. O. (LUBLIN–RZESZOW, 2014)
The feature of the research is the proposed fuzzy models representation method by means of relational systems, which unlike the known approaches, can solve integrated data mining problems in databases and fuzzy systems.
Keywords: fuzzy set; fuzzy logic; fuzzy relational databases; intelligent systems; data mining